PEMBERDAYAAN MASYARAKAT BERDASARKAN PENDEKATAN KEPERAWATAN MELALUI TANAMAN OBAT KELUARGA KHAS SUKU KAILI DA’A - Hidayat, Elin; Irnawan, Sri Marnianti; Claudia, Sindy (EJOIN : Jurnal Pengabdian Masyarakat, 2023)
This community service is carried out in the village of Doda, Central Sulawesi, which is a village inhabited by the majority of the Kaili da'a tribe and is a native tribe of the city of Palu. The residents of Kaili Da'a, Doda Village, live in the mountains of Palu City, which is quite far from the city center, so access to health services is also quite far. The people of the Kaili Da'a tribe like to use medicinal plants passed down from generation to generation from their tribe, but currently the lack of knowledge and interest of the community is decreasing in the cultivation of these medicinal plants even though the medicinal properties of their tribe are quite efficacious. The location of the village which is far from the city center allows them to have minimal access to medicines when emergencies occur. The method we apply is to re-empower these medicinal plants in the form of family medicinal plants which are planted in the yards of residents' houses with types of medicine including Sida rhombifolia, Ricinus communis, Jatropha curcas, Coleus atropurpureus, Andrographis paniculata and Alpinia galanga. The result is that these plants are very useful to help people when they need medicines during an emergency. In addition, we also provide explanations regarding the benefits of using these drugs to the public.